Development of Werewolf Game Media To Improve Students' Social Skills - Wanda Afiffah; Raudah Zaimah Dalimunthe; Meilla Dwi Nurmala (GUIDING WORLD (BIMBINGAN DAN KONSELING), 2025)
The research is based on the low social skills of students, especially at SMAN 4 Kota Serang, as found that students only socialize with their group friends, are passive when discussing, passive when friends need help and do not accept reprimands from friends. Efforts made to improve students' social skills include playing games. One of the potential games to utilize is the werewolf game. This study, therefore, aims to enhance social skill through the development of werewolf game-based media. The research employs a research and development (R&D) approach, using the Thiagarajan 4D model, which includes the stages of define, design, develop, and dissemination. The results of the study obtained from the product feasibility test obtained an average score of 86% with the category "Very Eligible". Then continued with a limited trial to 10 students of class XI SMAN 4 Kota Serang who have low social skills and are willing. The average score results from the limited trial were 81% in the category "Very Eligible". In addition, the media developed from pre-test and post-test score data. The N-Gain score results obtained on the werewolf game media to improve social skills were 57,9% which means that the media developed is in the moderate or quite effective category. It can be concluded that the development of werewolf games to improve social skills can be an innovation in Guidance and Counseling media that can be implemented by Guidance and Counseling teachers in school.